Is the Peltogyne gracilipes monodominant forest characterised by distinct soils? - Nascimento, Marcelo Trindade; Barbosa, Reinaldo Imbrozio; Dexter, Kyle Graham; Castilho, Carolina Volkmer de; Carvalho, Lidiany Camila da Silva; Villela, Dora Maria (Acta Oecologica, 2017)
Various explanations have been put forward for monodominance in otherwise diverse tropical forests. This study assesses if the monodominance of Peltogyne gracilipes on Maraca Island in the northern Amazon can be related to edaphic factors. The basal area of P. gracilipes and the five other most common tree species on Maraca Island (Astrocaryum aculeatum, Attalea maripa, Ecclinusa guianensis, Licania kunthiana and Pradosia surinamensis) were recorded in 30 regularly-spaced 0.5 ha plots distributed over an area of 25 km2, for which data on topography and concentration of mineral elements in the soil were also obtained. Stems of P. gracilipes accounted for ≥50% of the basal area in five of the plots, which we consider indicative of monodominance, whilst the highest relative basal area that any of the other species achieved in any plot was 31%. The soils data explained more of the variation in the basal area of P. gracilipes than it did for the other five species. The presence vs. absence and basal area of P. gracilipes was positively related to concentrations of magnesium (Mg), aluminium (Al), iron (Fe), phosphorus (P) and silt in the soil and to Mg:Ca ratios. These soils were found in the plots at the lowest elevations, which suggests that drainage factors may also be important. Overall, our results suggest that edaphic factors may explain, at least partially, monodominance in this Amazonian forest. © 2017 Elsevier Masson SAS
Keywords: Basal Area; Dicotyledon; Forest Ecosystem; Soil Nutrient; Soil-vegetation Interaction; Tropical Forest; Amapa; Amazonia; Maraca Island [amapa]; Astrocaryum Aculeatum; Attalea; Ecclinusa Guianensis; Licania Kunthiana; Peltogyne Gracilipes; Pradosia Surinamensis